CLIMATE CHANGE AND LIVELIHOOD: THE TWO SIDES OF A COIN - Odufuwa, B.O; Odufuwa, B.A; Fasina, S.O (Faculty of Geography, Universitas Gadjah Mada, 2012)
The economic, social, cultural and physical environment of man is interrelated with climatechange. This can be justified by several cities and people, particularly in developingcountries facing alarming threats of climate change. Scholars affirmed that low or poorcapacity to mitigate climate change in most developing cities would in long term swamp thenatural and human capacity systems required to adapt to prevailing impacts of climatechange. The impacts of climatic change on socio-economic activities have being a disturbingdevelopmental issue for governments in developed and developing world. In Most countriesclimate change is a notable environmental factor that shape and re-shape sources oflivelihoods. It has over time forced vast number of people into shackle of poverty throughdestruction of their means of livelihoods. This in recent time manifested in the lost ofproperties, lives, and destruction of infrastructural facilities. This paper unveiled the nexusbetween global climate change and livelihoods. It explored the concepts of livelihood andvulnerability in relation to climate change and its consequent impacts on livelihoods. Thepaper also examines the roles of governance towards adapting and mitigating the effects ofclimate change. It emphasized the need for improved infrastructural facilities, environmentaleducation/ enhanced climate change awareness programme, improved and monitor physicalplanning activities, good/effective governance and establishment of climate change insurancescheme.